Greening the power generation sector: Understanding the role of uncertainty - Romano, Teresa; Fumagalli, Elena (Renewable & sustainable energy reviews, 2018)
The transition to low-carbon technologies is essential to meet international climate change agreements. While market dynamics are contributing to make technologies increasingly affordable, experience has shown that other factors as well play a role in investment decisions. Uncertainty is one of them. Focusing on the power generation sector, this paper reviews the most recent literature on the subject, under the specific conditions that at least one adoption driver is uncertain and that a technology and/or environmental policy is in place. To understand how uncertainty affects adoption decisions, the survey considers economic parameters (e.g., investment costs or electricity prices) first and then focuses on the role of policy. While the deterring effect of uncertainty over investments is largely confirmed, several mitigating and underexplored issues are also identified, such as the role of heterogeneous investors’ characteristics or the welfare implications of different policy designs. Moreover, by explicitly considering policy uncertainty, this survey provides a clearer understanding of the effects of a lack of government commitment on the adoption of environmentally friendly technologies in the energy sector. Related challenges for policymakers and investors are carefully delineated, together with directions for further research. •Economic and policy uncertainty plays a crucial role in the energy transition.•The deterring effect of uncertainty over adoption of green technologies is confirmed.•Mitigating factors include investors’ characteristics and technological change.•Besides stability, policy design features and complementarity are highly relevant.•Investor heterogeneity and welfare effects of policy interventions need more inquiry.